Desafios da gestão social : as experiências no território do sertão ocidental sergipano - Santos, Plínio Elkson dos (2014)
The issue of the Social Management of the Territory has been widely discussed both in Brazil and in other countries. It´s a recurring management model, defined as an territorial innovation, and of policy management in construction. This question arises to end the reductionist view of the historical subject and proposes, without obliterating the importance of economic and environmental sustainability. The process of territorial development has in the State their protagonist, without losing the centrality no longer have a monopoly of power to in articulation with organized civil society - plan, set guidelines and make decisions capable of enhancing the wealth, in the broad sense of the place. Is a concept that incorporates a deliberative citizenship, which encourages and empowers civil society participation in policy decisions and regulations, or at least, attracts protagonists to collective actions and rightful inclusion in decisions and processes that have like characteristic the common good to the citizens of the territory and target a participatory equality under the sign of Social Management. To research the following methodological procedures were performed: technical visits and participant observation in reunions of the Board, application of questionnaires and interviews with semi-structured questions, beyond the panning of information and secondary data. From this view, the screen work emerges of the institutional arrangement embodied in the Territorial Board of the Sertão Occidental of Sergipe, with emphasis on the process of constitution, contradictions and limits, especially in spatial organization, in the infighting and the materiality of the projects. The intention is to study and know the progress and effectiveness of the actions pushed by the Territorial Board, noting the internal dynamics of its social actors and development expectations. What sets to infer that we are in a land, in analytical terms, mined, according to the multidimensionality of approaches and different prisms chosen and their results and differentiated products. What makes difficult the arrangement analytical to develop |more one study| about |rural territories|. We must transcend the obvious.